Preserving heritage, nurturing progress, raising social equity: Policy advice on how indigenous peoples can advance sustainable agriculture in Kenya - Fisher, Eleanor; Ohenjo, Nyang'ori; Ng'endo, Mary; Hellin, Jon (Nordic Africa Institute, 2023)
Recognising and including the knowledge and leadership of indigenous peoples in building resilient food systems is crucial for equitable transformation. Kenyan decision makers must empower indigenous peoples to engage in local climate adaptation and agricultural sector planning, and at the same time protect those peoples’ rights.